Corporate Social Responsibility Program of PT Pertamina EP Jambi Field: Community Welfare through the Gerai Energi (Green Edu Agrowisata Rumbai Energi) Program in Kenali Asam Atas Village, Jambi City - Afrianto; M. Zainul Arifin; Lutfia Nur Hidayah; Safrida (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2024)
Climate change poses a significant threat to Indonesia, including Jambi City. This issue is exacerbated by large-scale land conversion, leading to the shrinking of agricultural areas. In response, PT Pertamina EP Jambi Field has implemented the Gerai Energi (Green Edu Agrowisata Rumbai Energi) CSR program in Kenali Asam Atas Village, Jambi City. This study employed a descriptive qualitative approach, with data collected through interviews with program beneficiaries and stakeholders, program observation, and corporate documentation (strategic plans, work plans, monitoring reports, evaluation reports, and media coverage). Data sources were selected through purposive and snowball sampling. The findings indicate that the Gerai Energi program has had a tangible impact on improving the local economy. Additionally, the program was developed with an environmentally friendly approach, featuring the use of solar cells and a Liquid Fertilizer Generator Bioreactor (BPPC). This program also supports PT Pertamina EP Jambi Field’s operational activities, as the Gerai Energi program in the Ring I area of PT Pertamina EP Jambi Field has fostered a sense of ownership and mutual care for the production facilities within the community, ensuring smooth company operations.